Chronicle of a humanitarian pardon (with a right of grace) foretold - Rodríguez Gómez, Edgardo (EUNOMÍA. Revista en Cultura de la Legalidad, 2018)
Abstract: This article reviews the political and administrative process that ended with the humanitarian pardon and the right of grace signed by the former President of Peru, Pedro Pablo Kuczynski. His decision favoured Alberto Fujimori Fujimori, who was sentenced for grave human rights violations committed during his mandate as the head of the Peruvian government in 1990’s. Some legal and political arguments, held by high legal officers of the Ministry of Justice and Human Rights warning the top authorities about impunity guaranteed by this decision, are revealed.